The role of litigation in tobacco control El papel del litigio en el control del tabaco - Marlo Miura; Richard A. Daynard; Jonathan M. Samet (Instituto Nacional de Salud Pública, 2006)
There is now 50-years of experience in the United States litigating against the tobacco industry. As the base of evidence regarding health effects has evolved and new legal strategies have emerged, successive waves of litigation have occurred. The many failures by the first and second waves were followed by some notable successes in the third. Litigation by flight attendants and the states led to substantial settlements and some beneficial consequences for tobacco control. One of the most significant consequences of state litigation was access to the industry's documents, gained through the Minnesota settlement. These documents further empowered the tobacco control movement and strengthened the basis for legal action. The continuing litigation in the United States remains a threat to the industry, in spite of the mixed outcomes of recent cases. Existe en los Estados Unidos una experiencia 50 años de litigios contra la industria del tabaco. La base de evidencia recopilada en relación con los efectos de la salud ha respaldado una nueva estrategia legal, lo que a su vez ha desencadenado sucesivas oleadas de conflicto. Los errores de la primera y segunda oleada fueron relevados por algunos éxitos notables en la tercera. Asimismo, los pleitos con asistentes de vuelos y con los estados condujeron al establecimiento substancial de algunos beneficios para controlar el consumo de tabaco. Uno de los resultados más significativos de litigio estatal ganado en el estado de Minnesota fue el acceso a los documentos de la industria. Estos documentos fomentaron el movimiento del control del tabaco y consolidaron la base para su demanda legal. Así, el continuo pleito en los Estados Unidos sigue siendo una amenaza para la industria tabacalera, a pesar de los resultados contradictorios de casos recientes.